POTENCY OF ANTIOXIDANT, ANTICHOLESTEROL AND PLATELET ANTIAGGREGATION OF BLACK TEA (Camelia sinensis ) - Wahyu Widowati; Tati Herlina; Hana Ratnawati; Tjandrawati Mozef; Victor Immanuel (Buletin Penelitian Tanaman Rempah dan Obat, 2011)
Epidemiological studies have shown an in-verse correlation betweendiets rich in po-lyphenols, flavonoids and reduced risk of cardiovasculardisease. These associationswere mainly ascribed to the antioxidant, antiaggregation and anticholesterol capa-city of polyphenols. This association has been explained that atherogenesis is ini-tiated by hypercholesterol, lipid peroxida-tion and hyper aggregation platelet. The research was carried out to evaluate anti-oxidant, anticholesterol and antiaggrega-tion activities of methanol extract and frac-tions of black tea (Camelia sinensis). To evaluate antioxidant activity of methanol extract and fractions were compared  with (-)-Epigallocatechine 3-gallate (EGCG), an-ticholesterol activity were compared with simvastatin and antiaggregation activity were compared with aspirin. Antioxidant activity using the 1,1-diphenyl-2-picryl-hy-drazyl (DPPH) free radical scavenging acti-vity at two concentrations 100 µg/mL, 50 µg/mL and anticholesterol was cholesterol oxidase activity at two concentrations 0.005 µg/mL, 0.0025 µg/mL, the antiag-gregation  activity  used epinephrine (EPN)agonist at two concentrations 300 μM, 75 μM and one concentration 37.1 µg/mL of methanol extract and fractions of black tea. To know the difference of treatment, the data were analysed using Analysis of Variance (ANOVA) and be continued Dun-can’s new multiple range test. The results showed that DPPH scavenging activity were high (88.59-93.556%), the anticho-lesterol showed high activity (93.663-97.434%) and the antiaggregation sho-wed low up to high activity (79.967-4.31%). Using Duncan’s new multiple ra-nge test showed that anti-oxidant activity were not different among extract and fractions of black tea,the highest anti-cholesterol activity was black tea extract 0.005 µg/mL (97.434%) and the highest antiaggregation activity was ethyl acetate fraction on 75 μM EPN agonist (4.310 %), water fraction 37.1 µg/mL with 300 μM EPN agonist (21.833%).